The Macregol Gospels or The Rushworth Gospels edition of the Latin text with the Old English interlinear gloss transcribed from Oxford Bodleian Library, MS Auctarium D. 2. 19 - Tamoto, Kenichi, 1950- (Amsterdam/Philadelphia : John Benjamins Publishing Company, 2013)
This work is composed of two parts. The first or introductory part, contains a palaeographical discussion about Bodleian Library, MS Auctarium D.2.19, that is to say, the MacRegol Gospels or the Rushworth Gospels, edited by Kenichi Tamoto, and which forms the second and main part of this book. The provenience of the MS, the Latin text, the use of the MS, and the Old English gloss are discussed in detail in the introductory part. The chief aim that the author set himself is firstly to survey preceding printed versions of the MS, such as Stevenson & Waring (1856-65) and W.W. Skeat (1871-87), and
Description based upon print version of record.
Keywords: Bible. Gospels. English (Old English).; Bible. Gospels. Latin; Manuscripts, English (Old) -- Facsimiles; Manuscripts, English (Old).; RELIGION / Biblical Studies / Jesus, the Gospels & Acts; RELIGION / Biblical Studies / New Testament; Bible; Bible; Manuscripts, English (Old); Manuscripts, English (Old) -- Facsimiles; Electronic books